Follicular Unit Excision (FUE) Basics - Lam, Samuel M. (Facial Plastic Surgery, 2023)
Follicular unit excision (FUE) has risen to the forefront as the world's most popular hair transplant procedure. However, most writing on this subject has catered to the advanced practitioner. The goal of this article will be to focus on safe planning and decision making along with key technical steps that will guide the beginner surgeon to harvest a graft safely and to harvest the donor area in a uniform way to avoid overharvesting. Topics covered in this article also include instrumentation and decision making between FUE versus linear strip excision.
Keywords: follicular unit excision (FUE); basics; hybrid punch; oscillating; overharvesting; linear strip excision (LSE)